Cellulose Synthase (CesA) Genes in the Green Alga Mesotaenium caldariorum - Roberts, Alison W. (American Society for Microbiology, 2002)
Cellulose, a microfibrillar polysaccharide consisting of bundles of β-1,4-glucan chains, is a major component of plant and most algal cell walls and is also synthesized by some prokaryotes. Seed plants and bacteria differ in the structures of their membrane terminal complexes that make cellulose and, in turn, control the dimensions of the microfibrils produced. They also differ in the domain structures of their CesA gene products (the catalytic subunit of cellulose synthase), which have been localized to terminal complexes and appear to help maintain terminal complex structure. Terminal complex structures in algae range from rosettes (plant-like) to linear forms (bacterium-like). Thus, algal CesA genes may reveal domains that control terminal complex assembly and microfibril structure. The CesA genes from the alga Mesotaenium caldariorum, a member of the order Zygnematales, which have rosette terminal complexes, are remarkably similar to seed plant CesAs, with deduced amino acid sequence identities of up to 59%. In addition to the putative transmembrane helices and the D-D-D-QXXRW motif shared by all known CesA gene products, M. caldariorum and seed plant CesAs share a region conserved among plants, an N-terminal zinc-binding domain, and a variable or class-specific region. This indicates that the domains that characterize seed plant CesAs arose prior to the evolution of land plants and may play a role in maintaining the structures of rosette terminal complexes. The CesA genes identified in M. caldariorum are the first reported for any eukaryotic alga and will provide a basis for analyzing the CesA genes of algae with different types of terminal complexes.